Advances in Pharmacological Activities and Mechanisms of Glycyrrhizic Acid - Chen, Kun; Yang, Rong; Shen, Fa-Qian; Zhu, Hai-Liang (Current Medicinal Chemistry, 2020)
Licorice (Glycyrrhiza glabra L.) is widely regarded as an important medicinal plant and has been used for centuries in traditional medicine because of its therapeutic properties. Studies have shown that metabolites isolated from licorice have many pharmacological activities, such as antiinflammatory, anti-viral, participation in immune regulation, anti-tumor and other activities. This article gives an overview of the pharmacological activities and mechanisms of licorice metabolites and the adverse reactions that need attention. This review helps to further investigate the possibility of licorice as a potential drug for various diseases. It is hoped that this review can provide a relevant theoretical basis for relevant scholars’ research and their own learning.
Keywords: glycyrrhizic acid